2019
DOI: 10.22159/ajpcr.2019.v12i1.28808
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis: The Antimicrobial and Antioxidant Activity of Zinc Oxide Nanoparticles From Curcuma Longa

Abstract: Objective: Curcuma longa is a known natural medicine for inflammation from ancient times. It has a low absorption rate and poor solubility. Hence, it is used for the green synthesis of nanoparticles. Zinc oxide nanoparticle (ZnO NPs) is famous nanoparticles which are economical, less toxic, and brilliantly biocompatible. They have potential biomedical properties, mainly anticancer, antidiabetic, and antimicrobial.Methods: The present study was designed to investigate in vitro analysis of the antimicrobial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 30 publications
(31 reference statements)
1
3
1
Order By: Relevance
“…Gallic acid was taken as a standard material and showed IC 50 value of 16.65 µg mL −1 (R 2 = 0.587). This antioxidant activity against DPPH • is better or at least comparable to that (~70%) previously reported for Curcuma longa-mediated ZnO particles with the same concentration [61].…”
Section: Dpph Scavenging Assaysupporting
confidence: 87%
See 1 more Smart Citation
“…Gallic acid was taken as a standard material and showed IC 50 value of 16.65 µg mL −1 (R 2 = 0.587). This antioxidant activity against DPPH • is better or at least comparable to that (~70%) previously reported for Curcuma longa-mediated ZnO particles with the same concentration [61].…”
Section: Dpph Scavenging Assaysupporting
confidence: 87%
“…Analysis of the inhibition percentages revealed IC 50 values of 55.26 µg mL −1 (R 2 = 0.792) and 20.87 µg mL −1 (R 2 = 0.825) for ZnO@OFE NPs and gallic acid, respectively. An antioxidant efficacy of 81% was achieved for 200 µg mL −1 of ZnO@OFE NPs, which outperforms that previously reported (~70%) for Curcuma longa-assisted ZnO NPs using the same concentration [61].…”
Section: Hydrogen Peroxide Scavenging Assaycontrasting
confidence: 61%
“…The broad particle size distribution is mostly due to particle size aggregation, which is mainly related to the electrostatic attraction of zinc oxide nanoparticles [ 48 ]. It was reported that the biosynthesised zinc oxide nanoparticles from Curcuma longa rhizomes exhibited a spherical shape with a diameter of 25 nm [ 49 ]. Another study synthesised zinc oxide nanoparticles using casein as a capping agent and conjugated curcumin on their surfaces with a diameter of 12.8 nm and a zeta potential of −23.9 mV, and the particles remained stable in the solution [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Stan et al [ 54 ], the scavenging activity of zinc oxide nanoparticles is size-dependent, where the smallest size displayed the highest antiradical activity [ 54 ]. Zinc oxide nanoparticles using Curcuma longa rhizomes exhibited good antiradical activity, almost 70% at 200 µg/mL [ 49 ]. The antioxidant activity of curcumin-ZnO NPs demonstrates moderate activity by scavenging 70% at 2 mg/mL [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…38 The antioxidant property of ZnO-NPs could be resulted from the transfer of electron density located at oxygen to the odd electron located at nitrogen atom in DPPH. 39 This characteristic is dependent on the structural configuration of oxygen atom, and it determines the thermal stability of nanoparticle. 40 In addition, the antioxidant efficacy of ZnO-NPs against DPPH is likely due to the electrostatic attraction between positively charged NPs (ZnO = Zn 2+ + O 2 ) of plant extracts and negatively charged bioactive compounds (COO -, O -).…”
Section: Discussionmentioning
confidence: 99%